Three new species of Dicephalospora from China as revealed by morphological and molecular evidences - Huan-Di Zheng; Wen-Ying Zhuang (MycoKeys, 2019)
Three new species of Dicephalospora are introduced based on morphological characters and DNA sequence analyses (maximum parsimony and neighbor-joining methods), viz. D. albolutea, D. shennongjiana, and D. yunnanica. All of them lack mucilaginous caps at ascospore poles. Dicephalospora albolutea is distinguished by cream to yellowish white apothecia and slightly curved ascospores. Dicephalospora shennongjiana is characterized by yellow apothecia, elliptical-fusoid ascospores 19−22 × 7−8.8 μm, and J+ asci 130−150 × 14−16.5 μm. Dicephalospora yunnanica is distinguished by orange apothecia and fusoid ascospores 16.5−25.3 × 3.3−3.5 μm. Descriptions and illustrations of the new species as well as a key to the known species in the genus are provided.